Effect of the Number of Repetitions on Flexibility in Static Stretching with Unified Total Extension Time - MYOTSUZONO, Ryota; KUNIEDA, Yuika; TATSUMI, Yasutaka; NISHIYAMA, Yuta; KUBO, Seiji (Rigaku ryoho kagaku, 2025)
[Purpose] The effect of the number of repetitions on flexibility in static stretching with unified total extension time was investigated. [Participants and Methods] The study subjects were 10 healthy students (5 males and 5 females) attending a sports university. The total stretching time was standardized to 90 seconds. Flexibility was compared between a no-repetition condition of 90 seconds of stretching and a repetition condition of three sets of 30-second stretching. [Results] Significant increases in flexibility were observed after stretching in both conditions, but the rate of change in flexibility was not significantly different between the conditions. [Conclusion] There was no difference in the improvement of flexibility with or without repetitions in stretching with a uniform total extension time.